(untitled) (Ameghiniana, 2013)
In this third part, the palynological study of the sediments from the lower member of the Lagares Formation is completed with the descriptíon of spores of the infraturma Apiculati, Murornati, Monopseudosacciti, Laevigatomonoleti and pollen of the subturma Monosaccites and Disaccites. Síxteen species of spores and pollen grains, five of which are new (Apiculiretusispora coalescens, Microreticulatisporites inaequalis, Endosporites rhytidosaccus, Florinites flaccidus and Perisaccus angustus), have been described. On the basis of the analisis of the stratigraphical distriution of species recorded previously and genera of the new or indeterminate species, it is concluded that the most probable age of the microflora is Lower Namurian.